The Contribution of Communication and Digital Literacy Skills to Critical Thinking - Astuti Muh. Amin*; Romi Adiansyah; Noor Hujjatusnaini (Universitas Syiah Kuala, 2023)
The contribution of communication and digital literacy skills to critical thinking in biology are rarely explored. The present study employed a correlational research design to determine how communication and digital literacy skills contributed to students’ critical thinking. In this study, communication and digital literacy skills served as the predictor variables, whereas critical thinking served as the criterion variable. Fourth semester students from Tadris Biology department at IAIN Ternate in North Maluku made up the research sample. Essay questions, questionnaires, and observation sheets were used to collect data. Research results show that communication skills and digital literacy simultaneously and significantly affect critical thinking skills. The study’s findings proved that communication skills and digital literacy contribute to critical thinking skills as much as 34.93% and 29.67%, respectively. These findings indicate that educators need to incorporate components of communication skills and digital literacy into their instruction in order to enhance students’ critical thinking skills.